THE SUSTAINABILITY ANALYSIS OF THE CHRYSANTHEMUM FLOWER BUSINESS IN BANDUNGAN SUB-DISTRICT SEMARANG DISTRICT - Malihatun, Ira; Sumekar, Wulan; Legowo, Anang Mohamad (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Chrysanthemums are ornamental plants with the most production in Indonesia in 2021, amounting to 344,031,088 stalks. One of the largest chrysanthemum producers in Indonesia is the province of Central Java. Bandungan District, Semarang Regency is the largest contributor to chrysanthemum production in Central Java. Bandungan District has a harvest area of 1,692,000 m2 and the highest chrysanthemum production of 121,135,000 stalks compared to other districts, but the productivity is low at 71 stalks / m2 and has an impact on the low profits obtained by chrysanthemum flower farmers. The chrysanthemum business in Bandungan District has the potential to continue to be increased. This can be seen from the strategic role of Bandungan District as the main producer of chrysanthemums in Semarang Regency and in Central Java Province. The demand for chrysanthemum flowers in the market is very high, resulting in the growth of the chrysanthemum flower business is increasing. So efforts are needed to realize the sustainability of the chrysanthemum flower business. The study aims to analyze the sustainability of the chrysanthemum business in terms of social, economic and environmental aspects. The number of samples taken was 72 chrysanthemum farmers by proportional randomsampling in three villages which represented the largest land area. Multidimensional Scaling (MDS) analysis with theRapfish approach is used to see the sustainability status of the chrysanthemum business based on three dimensions, namely social, economic and environmental aspects. Based on the results of the study, the status of the social dimension of thesustainability of the chrysanthemum flower business is classified as less sustainable, with a score of 46.53; the status of the economic dimension is classified as good or very sustainable, the value is 88.35; and the status of the environmental dimension is classified as less sustainable, the value is 27.94.